An unfair semi-greedy real-time multiprocessor scheduling algorithm - Alhussian, Hitham; Zakaria, Nordin; Patel, Ahmed (Computers & electrical engineering, 2016)
Most real-time multiprocessor scheduling algorithms for achieving optimal processor utilization, adhere to the fairness rule. Accordingly, tasks are executed in proportion to their utilizations at each time quantum or at the end of each time slice in a fluid schedule model. Obeying the fairness rule results in a large number of scheduling overheads, which affect the practicality of the algorithm. This paper presents a new algorithm for scheduling independent real-time tasks on multiprocessors, which produces very few scheduling overheads while maintaining high schedulability. The algorithm is designed by totally relaxing the fairness rule and adopting a new semi-greedy criterion instead. Simulations have shown promising results, i.e. the scheduling overheads generated by the proposed algorithm are significantly fewer than those generated by state-of-the-art algorithms. Although the proposed algorithm sometimes misses a few deadlines, these are sufficiently few to be tolerated in view of the considerable reduction achieved in the scheduling overheads.